1993
DOI: 10.1103/physreva.48.1292
|View full text |Cite
|
Sign up to set email alerts
|

Double electron capture inNe8+-He collisions at intermediate energies

Abstract: High-resolution Auger spectra of doubly excited Be-like neon have been obtained for intermediate collisional velocities (0.89 -1.79 a.u. ). Ne was produced at high voltage in the Argonne National Laboratory electron-cyclotron-resonance ion source. A differentially pumped helium gas cell was used to study double electron capture. The LMX Auger decays of the Be-like neon are observed with a high-resolution 0' tandem electron spectrometer. High-angular-momentum states are observed to be populated during the colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…However, as the collision velocity is raised, more angular momentum is brought into the collision. For a given transition radius R, characteristic of populating a particular final n, the product mvR increases with v. Such a trend is well established previously [24,25,32,33). Generally, the larger the l of the transferred electrons, the smaller the probability for decay by autoionization [34].…”
Section: IIsupporting
confidence: 83%
See 1 more Smart Citation
“…However, as the collision velocity is raised, more angular momentum is brought into the collision. For a given transition radius R, characteristic of populating a particular final n, the product mvR increases with v. Such a trend is well established previously [24,25,32,33). Generally, the larger the l of the transferred electrons, the smaller the probability for decay by autoionization [34].…”
Section: IIsupporting
confidence: 83%
“…The overbarrier model of Niehaus, however, does not incorporate any velocity dependence in the capture cross section or predict the angular momentum distribution of the captured electrons. As the collisional velocity increases, higher angular momentum states are observed to be populated [24,25]. An attempt to include velocity dependent efFects in the MCBM was proposed and compared with experiments involving helium targets [26].…”
Section: Introductionmentioning
confidence: 99%
“…Seely et al (2017) found that autoionizing double capture can lead to an enhancement of X-ray emission following single capture. In addition, basic CX mechanisms for doubly excited state formation have been extensively studied in the keV energy range (Stolterfoht et al 1986;Winter et al 1987;Roncin et al 1989;Posthumus et al 1992;Raphaelian et al 1993;Chesnel et al 1996;Fléchard et al 2001;Zhang et al 2001Zhang et al , 2016Roncin 2020;Guo et al 2023). However, the collision energy dependence of doubly excited states has been sparsely reported for state-resolved double CX.…”
Section: Introductionmentioning
confidence: 99%
“…The same method of analysis was also applied to the analysis of the Ne 8+ + He spectrum by Langereis et al to test new calculations of Cornille [16]; as demonstrated recently, their identifications have been found to be often incorrect [21]; the accuracy of their identifications was not given by the authors. Finally, high-resolution electron spectra have also been published by other authors but without any detailed 1s 2 3lnl line identification [22][23][24].…”
Section: Introductionmentioning
confidence: 99%